Virulent Diuraphis noxia Aphids Over-Express Calcium Signaling Proteins to Overcome Defenses of Aphid-Resistant Wheat Plants - Sinha, Deepak K.; Chandran, Predeesh; Timm, Alicia E.; Aguirre-Rojas, Lina; Smith, C. Michael (My University, 2016)
The Russian wheat aphid, Diuraphis noxia, an invasive phytotoxic pest of wheat, Triticum aestivum, and barley, Hordeum vulgare, causes huge economic losses in Africa, South America, and North America. Most acceptable and ecologically beneficial aphid management strategies include selection and breeding of D. noxia-resistant varieties, and numerous D. noxia resistance genes have been identified in T. aestivum and H. vulgare. North American D. noxia biotype 1 is avirulent to T. aestivum varieties possessing Dn4 or Dn7 genes, while biotype 2 is virulent to Dn4 and avirulent to Dn7. The current investigation utilized next-generation RNAseq technology to reveal that biotype 2 over expresses proteins involved in calcium signaling, which activates phosphoinositide (PI) metabolism. Calcium signaling proteins comprised 36% of all transcripts identified in the two D. noxia biotypes. Depending on plant resistance gene-aphid biotype interaction, additional transcript groups included those involved in tissue growth; defense and stress response; zinc ion and related cofactor binding; and apoptosis. Activation of enzymes involved in PI metabolism by D. noxia biotype 2 aphids allows depletion of plant calcium that normally blocks aphid feeding sites in phloem sieve elements and enables successful, continuous feeding on plants resistant to avirulent biotype 1. Inhibition of the key enzyme phospholipase C significantly reduced biotype 2 salivation into phloem and phloem sap ingestion.
Citation: Sinha, D. K., Chandran, P., Timm, A. E., Aguirre-Rojas, L., & Smith, M. (2016). Virulent Diuraphis noxia Aphids Over-Express Calcium Signaling Proteins to Overcome Defenses of Aphid-Resistant Wheat Plants. PLoS One, 11(1), 20. doi:10.1371/journal.pone.0146809
Keywords: Hemiptera Aphididae; Russian Wheat; Acyrthosiphon-Pisum; Biotype 2; Feeding-Behavior; Artificial Diet